8. THE SUPERIORITY OF THE REMEDY BUYANG HUANWU TANG IN THE TREATMENT OF BLOOD STENOSIS (Vietnam Journal of Community Medicine, 2024)
Objectives: Learn more deeply and synthesize reviews of research on the clinical effects of Buyang huanwu tang medicine, and help clinicians know the rich and superior effects of our medicine, summarizes the authors’ research in recent years.Research methods: Literature review.Conclusion: Researching new therapeutic effects on different diseases, while creating and combining preparation methods to create new, easy-to-use preparations, is of great significance in clinical treatment. The medicine Buyang huanwu tang not only has a strong blood-boosting effect, a strict theoretical basis, and wide application are extremely great advantages. Contribute to improving the effectiveness of traditional medicine in the treatment of serious diseases of blood stasis.
Keywords: Buyang huanwu tang